2022
DOI: 10.1002/jdd.12849
|View full text |Cite
|
Sign up to set email alerts
|

Dental education practices during COVID‐19: A scoping review

Abstract: Introduction Dental education was brought to a halt with the emergence of coronavirus disease (COVID‐19). Traditional dental education comprised students working closely with instructors in a clinical laboratory setting; however, public health precautions necessitated a shift to a virtual learning platform. A scoping review of dental education practices since the start of the pandemic will help to understand approaches instructors have taken to provide dental education during this unprecedented ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…These techniques include but are not limited to: problem-based learning [ 19 , 20 ], flipped classroom [ 21 ], simulation [ 22 ], virtual reality and technology-enhanced learning [ 23 ], virtual and online education [ 4 ], and gamification [ 24 ]. COVID-19 pandemic has facilitated the emergence and enhancement of some of these methods [ 4 , 25 , 26 ]. Skills that belong to the domains of problem solving, self-study, and lifelong learning require improvement.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques include but are not limited to: problem-based learning [ 19 , 20 ], flipped classroom [ 21 ], simulation [ 22 ], virtual reality and technology-enhanced learning [ 23 ], virtual and online education [ 4 ], and gamification [ 24 ]. COVID-19 pandemic has facilitated the emergence and enhancement of some of these methods [ 4 , 25 , 26 ]. Skills that belong to the domains of problem solving, self-study, and lifelong learning require improvement.…”
Section: Discussionmentioning
confidence: 99%
“…11 In the present study, the objective was to apply the OSCE in face-to-face and virtual forms to the same group of students and to evaluate their performance, in line with the suggestion put forward in a 2022 scope review. 21 Furthermore, this suggested that studies should aim to compare traditional versus virtual education by means of students' grades, and in the literature, no studies were found that had compared these two modalities of OSCE evaluation. There was a significant difference in performance between OSCE and VOSCE, with OSCE showing better results.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of digital technology, educational platforms and applications has caused teaching and learning activities between educators and students to be carried out essentially through the use of digital technology. With the emergence of the COVID-19 pandemic, education worldwide changed drastically (26). In addition, in recent years, e-learning has emerged as a tool to improve dental education.…”
Section: Discussionmentioning
confidence: 99%
“…Dental education involves teaching the teacher's skills, both didactic and clinical, to students (26). Students observe the procedures that the instructors perform step by step, then perform the procedure on laboratory models, and then perform it on patients.…”
Section: Discussionmentioning
confidence: 99%